Ti-6al-4v titanium alloy based on zirconium hydride regulation and preparation method and application thereof
Patent Information
- Application Number
- CN202610942853.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-29
AI Technical Summary
[0006]针对现有技术中金属注射成形Ti-6Al-4V钛合金存在成形稳定性差、碳、氧含量高等问题,本发明的第一个目的是在于提供一种基于氢化锆调控的低碳低氧残留金属注射成形Ti-6Al-4V钛合金,且该材料中不存在脆性氧化物第二相,保持高强度的同时还具有优异的塑性性能
[0031] (1) The Ti-6Al-4V titanium alloy provided by the present invention has low carbon and oxygen content and no brittle oxide second phase. It has excellent plasticity and exhibits low oxygen content and high elongation after fracture at different sintering temperatures.
Smart Images

Figure CN122466308B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal injection molding technology, and relates to a Ti-6Al-4V titanium alloy based on zirconium hydride control, its preparation method and application. Background Technology
[0002] Ti-6Al-4V is one of the most widely used titanium alloys. Due to its high specific strength, excellent corrosion resistance, and good biocompatibility, it has significant application value in aerospace, medical implants, and lightweight or high-end equipment. With the continued growth in demand for complex small components and near-net-shape manufacturing, and given its advantages in preparing complex-shaped parts, high material utilization, and large-scale manufacturing, metal injection molding is considered an important potential method for fabricating precision titanium alloy components.
[0003] However, Ti-6Al-4V titanium alloy powder has high surface activity and is extremely sensitive to interstitial elements such as carbon and oxygen. During the metal injection molding process, on the one hand, titanium alloy powder easily reacts with oxygen or oxygen-containing substances in the environment during mixing, injection, debinding, and sintering, leading to an increase in oxygen content. On the other hand, the metal injection molding process requires the introduction of a high proportion of organic binders. If the binder is not sufficiently removed or the pyrolysis products are not properly discharged, it can easily lead to an increase in carbon and oxygen residues in the sintered body. Excessive oxygen content enhances the solid solution strengthening effect, increases dislocation movement resistance, and reduces the ability to coordinate plastic deformation; while excessive carbon content promotes the formation of carbides or localized carbon-rich regions, inducing crack initiation and propagation. Therefore, controlling carbon and oxygen residues is a crucial factor restricting the improvement of the overall performance of metal injection molded Ti-6Al-4V titanium alloys.
[0004] In existing technologies, additives with strong oxygen affinity are often used to regulate oxygen content in titanium alloy powder metallurgy products. However, some additives tend to form oxide second phases after sintering. While these second phases may reduce the dissolved oxygen content in the Ti matrix, they can also act as brittle inclusions or crack initiation sources, adversely affecting the plasticity, fatigue performance, and long-term service reliability of the sintered body. For example, Chinese patent application CN121826442A discloses a composite reinforced TC4 titanium alloy feedstock and a method for preparing titanium alloy materials. By adding a small amount of LaB6 powder, Si powder, and C powder to the Ti-6Al-4V feedstock, the carbon and oxygen residues in the titanium alloy are reduced. However, the carbon residue in this method is still relatively high, and brittle TiC and La2O3 second phases are formed in the sintered sample. On the other hand, if only the degreasing process or binder system is optimized to reduce residual carbon and oxygen, it is difficult to simultaneously ensure feed flowability, injection molding stability, degreasing efficiency and low impurity residue. For example, Chinese patent application CN121267181A discloses an oxygen control process for injection molding titanium alloys based on degreasing with an oxygen-free solvent. By introducing n-heptane or trichloroethylene as an oxygen-free solvent to the titanium alloy injection molding blank, the oxygen content of the sintered part can be reduced to below 0.268 wt.%, but the carbon content of the sintered part obtained by this method is still relatively high.
[0005] Therefore, there is an urgent need to develop a metal injection molding method for preparing Ti-6Al-4V titanium alloys that has good forming stability, is not prone to introducing brittle second phases, and can effectively reduce carbon and oxygen residues, so as to meet the needs of preparing high-performance Ti-6Al-4V titanium alloy precision and complex components. Summary of the Invention
[0006] To address the problems of poor forming stability and high carbon and oxygen content in existing metal injection molded Ti-6Al-4V titanium alloys, the first objective of this invention is to provide a low-carbon, low-oxygen residual metal injection molded Ti-6Al-4V titanium alloy based on zirconium hydride regulation. This material does not contain a brittle oxide second phase and maintains high strength while also exhibiting excellent plasticity.
[0007] The second objective of this invention is to provide a method for preparing Ti-6Al-4V titanium alloy based on zirconium hydride control. By introducing an appropriate amount of zirconium hydride powder and combining it with a specific binder system and a staged debinding and solution sintering process, the method effectively controls the carbon and oxygen residues in the Ti-6Al-4V sintered body, while avoiding the problem of traditional oxygen scavenging additives easily forming a brittle oxide second phase.
[0008] The third objective of this invention is to provide an application of a zirconium hydride-regulated Ti-6Al-4V titanium alloy, which can be used as a raw material in the preparation of titanium alloy components for medical devices to improve biocompatibility.
[0009] To achieve the above technical objectives, this invention provides a method for preparing Ti-6Al-4V titanium alloy based on zirconium hydride regulation, the method comprising the following steps:
[0010] S1 mixes Ti-6Al-4V powder and zirconium hydride powder, adds a binder, and kneads to obtain the feedstock;
[0011] The feed described in S2 is injection molded and catalytically degreased to obtain a catalytically degreased preform;
[0012] After hot degreasing and solution sintering, the catalytic degreased blank described in S3 is used to obtain Ti-6Al-4V titanium alloy; the Ti matrix of the Ti-6Al-4V titanium alloy contains Zr element dissolved in it.
[0013] The technical solution of this invention achieves synergistic control of carbon and oxygen residues in Ti-6Al-4V titanium alloys through the introduction of a small amount of zirconium hydride powder into the Ti-6Al-4V powder system. Specifically, this invention achieves uniform mixing of Ti-6Al-4V powder and zirconium hydride powder through powder mixing, and preferentially removes some organic polymers in the binder through catalytic degreasing, forming a continuous exhaust channel inside the billet; subsequently, during the heating process of thermal degreasing, zirconium hydride can undergo dehydrogenation transformation, and the released hydrogen helps to further improve the local atmosphere in the powder gaps and pore channels, promotes the discharge of carbon- and oxygen-containing small molecules generated by binder pyrolysis, and reduces the risk of their retention and re-adsorption on the surface of titanium alloy powder, particle contact interface, and near residual pores. Meanwhile, the Zr element formed after dehydrogenation has good solid solution compatibility with the Ti matrix under high-temperature sintering conditions. It can gradually diffuse into the Ti-6Al-4V matrix and form a solid solution state during solid solution sintering, thereby avoiding the problem of traditional strong oxygen removal additives easily forming brittle oxide second phases. As a result, a Ti-6Al-4V titanium alloy with low carbon and oxygen residues is obtained, and the plasticity of the titanium alloy is improved simultaneously without significantly sacrificing strength.
[0014] Experiments revealed that when Ti-6Al-4V raw material powder was used instead of intermediate alloy powder, the aforementioned effects could not be achieved. This is because the elemental powder mixture system requires simultaneous powder densification, Al / V element diffusion alloying into the Ti matrix, and composition homogenization during sintering. This process relies on high sintering temperatures or long holding times, easily leading to rapid grain boundary migration and significant grain coarsening, which is detrimental to the synergistic improvement of the sintered body's strength and plasticity. In contrast, this invention uses intermediate alloy Ti-6Al-4V powder as the matrix powder. Since Al and V elements are already alloyed, alloying does not require long-range diffusion of elemental Al and V powders during sintering. Sintering can be achieved at relatively low sintering temperatures, thereby reducing the risk of abnormal grain growth. Meanwhile, the intermediate alloy Ti-6Al-4V powder has a more stable initial composition and fewer heterogeneous powder reaction interfaces, which is beneficial for the release of hydrogen and residual Zr elements during the dehydrogenation process of zirconium hydride to effectively control the carbon and oxygen residues, and allows the dehydrogenated Zr elements to enter the Ti-6Al-4V matrix mainly in the form of solid solution diffusion, rather than forming a hard and brittle second phase.
[0015] As a preferred embodiment, in S1, the amount of zirconium hydride powder relative to the total mass of Ti-6Al-4V powder and zirconium hydride powder is greater than 0% and not more than 1%. In this invention, the amount of zirconium hydride powder has a direct impact on the performance of titanium alloys. Within the preferred range of this invention, it can exert the carbon and oxygen regulation effect while avoiding the enrichment of heterogeneous phases, uneven powder dispersion, or local component segregation caused by excessive addition.
[0016] Further preferably, in S1, the amount of zirconium hydride powder relative to the total mass of Ti-6Al-4V powder and zirconium hydride powder is 0.45~0.55%. Experiments have shown that within this further preferred addition range, the plasticity of the sintered body can be significantly improved while slightly sacrificing the strength of the titanium alloy. This is because a small amount of Zr dissolved into the Ti-6Al-4V matrix can improve local interfacial bonding and elemental distribution uniformity, while lower carbon and oxygen residues can weaken the adverse effects of interstitial elements on dislocation slip, grain boundary coordinated deformation, and crack propagation paths, thereby improving the plasticity tolerance of the sintered body.
[0017] As a preferred embodiment, the zirconium hydride powder has a particle size of less than or equal to 10 μm. Experiments have shown that when the particle size of the zirconium hydride powder is too small, the specific surface area increases, which easily increases the adsorption of oxygen-containing substances such as oxygen and moisture on the powder surface. Simultaneously, it leads to excessively rapid dehydrogenation, reducing the matching between the hydrogen release process and the degreasing, venting, and sintering neck formation processes. Conversely, when the particle size is too large, the effective reaction interface decreases, the diffusion distance of Zr into the Ti-6Al-4V matrix increases, and local Zr enrichment is easily formed.
[0018] As a preferred embodiment, in S1, the powder mixing conditions are as follows: powder is mixed by ball milling under inert gas protection, the ball-to-powder ratio is 1:(2~3), the ball milling speed is 150~250 r / min, and the ball milling time is not less than 10 h. The low-speed, long-duration ball milling of this invention can effectively achieve uniform mixing of the two powders, providing favorable conditions for subsequent uniform solution sintering.
[0019] As a preferred embodiment, in S1, the mixing temperature is 170~185℃, the mixing time is 2~3h, and the rotor speed is 20~30r / min.
[0020] As a preferred embodiment, in S1, the binder comprises polyoxymethylene, high-density polyethylene, ethylene-vinyl acetate, and stearic acid. This invention, by employing a polyoxymethylene-based binder system, achieves a balance between low residue, molding stability, and feed flowability.
[0021] In this invention, the density range of the high-density polyethylene is 0.93~0.97 g / cm³. 3 .
[0022] As a preferred embodiment, the total amount of Ti-6Al-4V powder and zirconium hydride powder is used in a mass ratio of (85~87):(13~15) to the binder. This allows for good feed flowability with only a small amount of binder.
[0023] As a preferred embodiment, the binder comprises, by weight percentage: 83-85% polyoxymethylene (POM), 1-3% high-density polyethylene (HDPE), 3-6% ethylene-vinyl acetate (EVA), and 8-10% stearic acid. In a further preferred binder composition, POM serves as the main binder, which can be preferentially removed via catalytic degreasing at lower temperatures, reducing the source of organic residues in subsequent high-temperature stages; a small amount of HDPE serves as the skeleton component, which helps maintain the shape stability of the catalytically degreased preform; the ethylene-vinyl acetate copolymer improves the toughness, compatibility, and feed flow behavior of the binder system; furthermore, stearic acid improves the wetting and dispersion state between the powder and the binder, reducing the tendency for powder agglomeration during mixing and injection molding.
[0024] As a preferred embodiment, in S2, the injection molding conditions are: temperature of 180~190℃ and pressure of 90~120MPa.
[0025] As a preferred embodiment, the catalytic degreasing uses oxalic acid vapor as a catalyst, and during the catalytic degreasing process, the temperature is increased to 110-115℃, 120-122℃, and 125-127℃ respectively at a heating rate of 0.5-1.5℃ / min, and held at each temperature range for 1.5-2.5 hours. The main purpose of the catalytic degreasing stage is to remove organic polymers such as polyoxymethylene from the binder system. Multi-stage catalytic degreasing at lower temperatures facilitates deep removal of the main binder, reducing the source of organic residues in the subsequent sintering stage.
[0026] As a preferred embodiment, in S3, the heating program for thermal degreasing is as follows: heating at a rate of 0.5~1.5℃ / min to four stages: 180~210℃, 320~350℃, 430~450℃, and 650~700℃, with each stage held for 0.3~0.8 hours. In this stage, the invention achieves pre-sintering during thermal degreasing. Multiple holding periods allow residual skeleton agents, plasticizers, and lubricants in the binder to gradually decompose and be discharged, reducing the risk of increased internal pressure, bubbling, cracking, and localized carbon residue caused by rapid heating or concentrated decomposition. Furthermore, the dehydrogenation transformation of zirconium hydride improves the local atmosphere within the powder gaps and pore channels, promoting the discharge of carbon- and oxygen-containing small molecules generated by binder pyrolysis. This degreasing method, in conjunction with the dehydrogenation behavior of zirconium hydride, enhances the discharge efficiency of carbon- and oxygen-containing volatiles.
[0027] As a preferred embodiment, the solid solution sintering conditions are as follows: after thermal degreasing, the temperature is further increased to 1000-1100℃ at a rate of 2-5℃ / min, and held for 6-8 hours. The solid solution sintering stage of this invention is a key step in achieving residual Zr solid solution diffusion based on the previous zirconium hydride dehydrogenation. During the initial heating process, zirconium hydride undergoes dehydrogenation, releasing hydrogen that further improves the local atmosphere within the powder gaps and pore channels, promotes the discharge of carbon- and oxygen-containing cracking products, and reduces their retention on the Ti-6Al-4V powder surface and near residual pores. This also reduces obstacles to Zr solid solution diffusion. Subsequently, in the solid solution sintering stage at 1000-1100℃, the Zr elements formed after dehydrogenation diffuse into the Ti-6Al-4V matrix and form a solid solution state, thereby reducing the risk of local Zr enrichment and the presence of a hard and brittle second phase. Experiments have shown that when the sintering temperature is too low or the holding time is too short, Zr diffusion homogenization is insufficient; while when the temperature is too high or the time is too long, it is easy to cause β grain growth, lamellar coarsening and stabilization of residual porosity, which are all detrimental to the comprehensive improvement of the plasticity and tensile strength of the sintered body.
[0028] The present invention also provides a Ti-6Al-4V titanium alloy based on zirconium hydride regulation, which is obtained by the above preparation method and has a carbon content of less than 0.109 wt.% and an oxygen content of less than 0.324 wt.%.
[0029] Finally, this invention also provides an application of a zirconium hydride-modified Ti-6Al-4V titanium alloy, which can be used as a raw material in the preparation of titanium alloy components for medical devices, thereby improving biocompatibility. It is particularly suitable for the preparation of intraoperative fixation aids, dental prosthetic components, or structural components for minimally invasive surgical instruments.
[0030] Compared with the prior art, the present invention has at least the following beneficial effects:
[0031] (1) The Ti-6Al-4V titanium alloy provided by the present invention has low carbon and oxygen content and no brittle oxide second phase. It has excellent plasticity and exhibits low oxygen content and high elongation after fracture at different sintering temperatures.
[0032] (2) The method for preparing Ti-6Al-4V titanium alloy provided by this invention introduces an appropriate amount of zirconium hydride powder, combines it with a specific binder system, and employs a staged debinding and solution sintering process. This effectively controls the residual carbon and oxygen in the Ti-6Al-4V sintered body through the dehydrogenation transformation of the zirconium hydride powder, while avoiding the problem of traditional oxygen-removing additives easily forming a brittle oxide second phase. Furthermore, the Zr element formed after dehydrogenation has good solid solution compatibility with the Ti matrix and can gradually diffuse into the Ti-6Al-4V matrix during sintering to form a solid solution state, thus improving the plasticity of the Ti-6Al-4V titanium alloy.
[0033] (3) The present invention uses a polyoxymethylene-based binder system composed of polyoxymethylene, high-density polyethylene, ethylene-vinyl acetate copolymer and stearic acid, which can take into account low residue, molding stability and feed flowability. Among them, polyoxymethylene, as the main binder, can be preferentially removed by catalytic degreasing at a lower temperature, reducing the source of organic residue in the subsequent high-temperature stage; a small amount of high-density polyethylene, as a skeleton component, is beneficial to maintaining the shape stability of the degreased preform; ethylene-vinyl acetate copolymer can improve the toughness, compatibility and feed flow behavior of the binder system; stearic acid can improve the wetting and dispersion state between powder and binder, and reduce the tendency of powder agglomeration during mixing and injection.
[0034] (4) This invention employs a staged degreasing system combining catalytic degreasing and thermal degreasing. In the catalytic degreasing stage, the polyoxymethylene (POM) main binder is preferentially removed, forming a continuous exhaust channel inside the green body. Subsequently, thermal degreasing at multiple temperature platforms gradually decomposes and discharges residual skeleton agents, plasticizers, and lubricants, thereby reducing the risk of increased internal pressure, bubbling, cracking, and localized carbon residue caused by rapid heating or concentrated decomposition. This staged degreasing method synergizes with the dehydrogenation behavior of zirconium hydride, which is beneficial for improving the discharge efficiency of carbon- and oxygen-containing volatiles. Attached Figure Description
[0035] Figure 1 The surface microstructure morphology of the sintered sample prepared in Example 2.
[0036] Figure 2 The surface microstructure morphology of the sintered sample prepared in Example 3.
[0037] Figure 3 The surface microstructure morphology of the sintered sample prepared in Example 4 is shown.
[0038] Figure 4 The surface microstructure morphology of the sintered sample prepared for Comparative Example 1 is shown.
[0039] Figure 5 The tensile property curves are for Examples 2-4 and Comparative Examples 1-3. Detailed Implementation
[0040] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0041] The high-density polyethylene used in the embodiments and comparative examples of this invention has a density of 0.949 g / cm³. 3 .
[0042] The Ti-6Al-4V master alloy powder used in the embodiments and comparative examples of this invention has a particle size of less than 20 μm (D 10 =5.51μm, D 50 =11.53μm, D 90 =19.55μm), its chemical composition by mass percentage is: Al 6.46%, V 4.22%, Fe 0.17%, O 0.136%, N 0.0099%, H 0.0051%, Si<0.01%, C 0.12%, balance Ti.
[0043] Example 1
[0044] Step 1: Weighing the raw materials
[0045] Ti-6Al-4V master alloy powder was selected as the matrix powder, and zirconium hydride powder with a particle size of less than 10 μm was selected as the additive powder. The binder used consisted of 85 wt.% polyoxymethylene, 1 wt.% high-density polyethylene, 6 wt.% ethylene-vinyl acetate and 8 wt.% stearic acid.
[0046] Prepare 3000g of a mixture of Ti-6Al-4V master alloy powder and zirconium hydride powder, wherein the amount of zirconium hydride powder added is 0.2wt.% of the total amount of the mixture, that is, 6g of zirconium hydride powder, 2994g of Ti-6Al-4V master alloy powder, and 492.9g of binder.
[0047] Step 2: Mixing the powders
[0048] Ti-6Al-4V master alloy powder and zirconium hydride powder were weighed and placed into a planetary ball mill for mixing. The mixing was carried out under argon protection, with a ball-to-material ratio of 1:2, a rotation speed of 200 r / min, and a mixing time of 10 h to obtain a uniformly mixed powder.
[0049] Step 3: Feed Preparation
[0050] The above 3000g of uniformly mixed powder and 492.9g of binder were placed into a mixer and mixed under argon protection throughout the process. The mixing temperature was 175℃, the rotor speed was 25r / min, and the mixing time was 3h. The resulting feed was obtained after mixing.
[0051] Step 4: Injection Molding
[0052] The above feed material is added to the barrel of the injection molding machine and injected into the mold at an injection temperature of 190℃ and an injection pressure of 120MPa to obtain an injection molded blank.
[0053] Step 5: Catalytic Degreasing
[0054] The above injection-molded preform was placed in an oxalic acid degreasing furnace and heated sequentially to 115°C, 120°C and 125°C at a heating rate of 1°C / min. The preform was then held at each temperature for 2 hours. After the catalytic degreasing was completed, the catalytically degreased preform was obtained.
[0055] Step Six: Thermal Degreasing and Solution Sintering
[0056] The above-mentioned catalytically degreased billet was placed in a graphite furnace and heated sequentially to 200℃, 320℃, 430℃, and 650℃ at a heating rate of 1.2℃ / min. It was then held at each temperature for 0.5h for hot degreasing. After that, it was heated to 1100℃ at a heating rate of 3℃ / min and held for 7.5h. Then it was cooled with the furnace to obtain a Ti-6Al-4V titanium alloy with Zr dissolved in the Ti matrix.
[0057] Example 2
[0058] This embodiment is basically the same as Embodiment 1, except that the amount of zirconium hydride powder added is 0.5 wt.% of the total amount of mixed powder, and the solid solution sintering temperature is 1000℃. Specifically, the weight of zirconium hydride powder added is 15g, and the weight of Ti-6Al-4V master alloy powder is 2985g; after steps one, two, three, four, and five, the temperature is raised sequentially to 200℃, 320℃, 430℃, and 650℃ at a heating rate of 1.2℃ / min, and held at each temperature for 0.5h for hot degreasing. Then, the temperature is raised to 1000℃ at a heating rate of 3℃ / min and held for 7.5h, followed by furnace cooling to obtain a Ti-6Al-4V titanium alloy with Zr element dissolved in the Ti matrix.
[0059] The surface micromorphology of this embodiment is as follows: Figure 1 As shown in the figure, no brittle second phase is formed. Figure 5 It can be seen that the titanium alloy in this embodiment has the highest elongation.
[0060] Example 3
[0061] This embodiment is basically the same as Embodiment 2, except that the solution sintering temperature in step six is 1050℃. Specifically, the catalytic degreasing blank obtained in Embodiment 2 is placed in a sintering furnace. First, the temperature is raised sequentially to 200℃, 320℃, 430℃, and 650℃ at a heating rate of 1.2℃ / min, and held at each temperature for 0.5h for hot degreasing. Then, the temperature is raised to 1050℃ at a heating rate of 3℃ / min and held for 7.5h. Subsequently, the furnace is cooled to obtain a Ti-6Al-4V titanium alloy with Zr dissolved in the Ti matrix.
[0062] The surface micromorphology of this embodiment is as follows: Figure 2 As shown, by Figure 2 It can be seen that no brittle second phase is formed.
[0063] Example 4
[0064] This embodiment is basically the same as Embodiment 2, except that the sintering temperature is 1100℃. Specifically, the catalytically degreased billet obtained in Embodiment 2 is placed in a sintering furnace. First, the temperature is raised sequentially to 200℃, 320℃, 430℃, and 650℃ at a heating rate of 1.2℃ / min, and held at each temperature for 0.5h for hot degreasing. Then, the temperature is raised to 1100℃ at a heating rate of 3℃ / min and held for 7.5h. Subsequently, the furnace is cooled to obtain a Ti-6Al-4V titanium alloy with Zr dissolved in the Ti matrix.
[0065] The surface micromorphology of this embodiment is as follows: Figure 3 As shown, by Figure 3 It can be seen that no brittle second phase is formed.
[0066] Example 5
[0067] This embodiment is basically the same as Embodiment 1, except that the amount of zirconium hydride powder added is 1 wt.% of the total amount of mixed powder. That is, the weight of zirconium hydride powder added is 30g, and the weight of Ti-6Al-4V master alloy powder is 2970g. After a series of processes in steps two, three, four, five, and six, a Ti-6Al-4V titanium alloy with Zr element dissolved in the Ti matrix is obtained.
[0068] Example 6
[0069] Step 1: Weighing the raw materials
[0070] Ti-6Al-4V master alloy powder was selected as the matrix powder, and zirconium hydride powder with a particle size of less than 5 μm was selected as the additive powder. The binder used consisted of 84 wt.% polyoxymethylene, 3 wt.% high-density polyethylene, 3 wt.% ethylene-vinyl acetate and 10 wt.% stearic acid.
[0071] Prepare 3000g of mixed powder, wherein the amount of zirconium hydride powder added is 0.5wt.% of the total amount of mixed powder, that is, the amount of zirconium hydride powder added is 15g, the amount of Ti-6Al-4V master alloy powder is 2985g, and the amount of binder is 492.9g.
[0072] Step 2: Mixing the powders
[0073] Ti-6Al-4V master alloy powder and zirconium hydride powder were weighed and placed into a planetary ball mill for mixing. The mixing was carried out under argon protection, with a ball-to-material ratio of 1:2, a rotation speed of 150 r / min, and a mixing time of 12 h to obtain a uniformly mixed powder.
[0074] Step 3: Feed Preparation
[0075] The above 3000g of uniformly mixed powder and 492.9g of binder were placed into a mixer and mixed under argon protection throughout the process. The mixing temperature was 180℃, the rotor speed was 25r / min, and the mixing time was 2.5h. The resulting feed was obtained after mixing.
[0076] Step 4: Injection Molding
[0077] The above feed material is added to the barrel of the injection molding machine and injected into the mold at an injection temperature of 185℃ and an injection pressure of 115MPa to obtain an injection molded blank.
[0078] Step 5: Catalytic Degreasing
[0079] The above injection-molded blank was placed in an oxalic acid degreasing furnace and heated to 115°C, 120°C and 125°C at a heating rate of 1°C / min. The temperature was then maintained at each temperature for 2 hours. After the catalytic degreasing was completed, the catalytically degreased blank was obtained.
[0080] Step Six: Thermal Degreasing and Solution Sintering
[0081] The above-mentioned catalytically degreased billet was placed in a graphite furnace and heated sequentially to 200℃, 350℃, 450℃, and 700℃ at a heating rate of 1℃ / min. It was then held at each temperature for 0.5h for hot degreasing. After that, it was heated to 1100℃ at a heating rate of 3℃ / min and held for 6h. Then it was cooled with the furnace to obtain a Ti-6Al-4V titanium alloy with Zr dissolved in the Ti matrix.
[0082] Example 7
[0083] The only difference between this embodiment and Embodiment 2 is that the amount of zirconium hydride powder is replaced with 2 wt.% of the total amount of mixed powder. All other steps and conditions are the same as in Embodiment 2, and Ti-6Al-4V titanium alloy is obtained.
[0084] Comparative Example 1
[0085] The only difference between this comparative example and Example 2 is that zirconium hydride powder is not added; all other steps and conditions are the same as in Example 2, resulting in a Ti-6Al-4V titanium alloy.
[0086] The surface micromorphology of the comparison example is as follows Figure 4 As shown. Although the tensile strength and yield strength of this comparative example are slightly increased due to the higher carbon and oxygen residues, its elongation is significantly lower than that of Example 2 under the same process conditions. In addition, the surface micromorphology shows that the surface morphology of the undoped comparative example is not significantly different from that of the examples, which also proves that the doped zirconium hydride of the present invention does not form a hard and brittle second phase.
[0087] Comparative Example 2
[0088] The only difference between this comparative example and Example 3 is that zirconium hydride powder is not added. All other steps and conditions are the same as in Example 3, resulting in a Ti-6Al-4V titanium alloy.
[0089] Comparative Example 3
[0090] The only difference between this comparative example and Example 4 is that zirconium hydride powder is not added. All other steps and conditions are the same as in Example 4, resulting in Ti-6Al-4V titanium alloy products.
[0091] Compared to Example 4, under the same process conditions, the elongation of the undoped zirconium hydride in this comparative example is significantly reduced.
[0092] Comparative Example 4
[0093] The only difference between this comparative example and Example 2 is that the Ti-6Al-4V master alloy powder was replaced with an equal mass of raw material powder mixed with zirconium hydride powder, and the titanium powder was replaced with hydrogenated dehydrogenated titanium powder. Specifically, 2686.5 g of hydrogenated dehydrogenated titanium powder (particle size less than 35 μm), 179.1 g of aluminum powder (less than 30 μm), 119.4 g of vanadium powder (5~25 μm), and 15 g of zirconium hydride powder (less than 10 μm) were placed in a ball mill jar in an argon-protected glove box. The sample was then prepared using the steps shown in Example 2.
[0094] Comparative Example 5
[0095] The only difference between this comparative example and Example 2 is that thermal degreasing is not performed. After step five is completed, solution sintering is performed directly to obtain Ti-6Al-4V titanium alloy.
[0096] The mechanical properties of each embodiment and comparative example are shown in Table 1.
[0097] Table 1: Mechanical Properties
[0098] As shown in the examples and comparative examples, under the same binder system and the same debinding and sintering process, although the tensile and yield strengths of the Ti-6Al-4V sintered body with added zirconium hydride decreased slightly in the sintering range of 1000~1100℃, it exhibited lower carbon and oxygen residues and higher elongation after fracture at the corresponding sintering temperatures. Furthermore, this reduction in carbon and oxygen content, and the avoidance of the formation of a hard and brittle second phase, is highly beneficial for improving the cyclic fatigue life of metal injection molded titanium alloys. Especially under the sintering condition of 1100℃, the elongation after fracture in Comparative Example 3 without added zirconium hydride decreased significantly, while Example 4 with added zirconium hydride maintained a high elongation after fracture, indicating that the zirconium hydride control method described in this invention can improve the plastic stability of the Ti-6Al-4V sintered body after high-temperature sintering.
[0099] Furthermore, as shown in Example 7, the addition of excessive zirconium hydride did not lead to a continuous decrease in C and O in the sintered body, nor did it further increase the elongation. This may be related to the increase in hydrogen partial pressure caused by the hydrogen decomposition of excessive zirconium hydride, which effectively reduces the hydrogen chemical potential energy in the sintering system, thereby inhibiting the decomposition and release of hydrogen by zirconium hydride, thus limiting the reduction of oxygen and carbon and the improvement of elongation.
[0100] The above results show that the present invention does not improve performance simply by increasing the sintering temperature or changing the binder composition, but achieves a balance between low carbon and low oxygen residue and high plasticity through the synergistic effect of zirconium hydride addition, low residual binder system and staged debinding sintering process.
[0101] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any equivalent substitutions, combinations, or improvements made to process parameters, raw material particle size, ball milling equipment, mold dimensions, sintering temperature, and application scenarios within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing Ti-6Al-4V titanium alloy based on zirconium hydride regulation, characterized in that: Includes the following steps: S1 mixes Ti-6Al-4V powder and zirconium hydride powder, then adds a binder and kneads to obtain a feedstock; the amount of zirconium hydride powder relative to the total mass of Ti-6Al-4V powder and zirconium hydride powder is 0.45~0.55%; the particle size of the zirconium hydride powder is less than or equal to 10μm. The feed described in S2 is injection molded and catalytically degreased to obtain a catalytically degreased preform; After the catalytic degreasing blank described in S3 is subjected to hot degreasing and solution sintering, Ti-6Al-4V titanium alloy is obtained; the Ti matrix of the Ti-6Al-4V titanium alloy contains Zr element dissolved in it. The conditions for solution sintering are as follows: after hot degreasing, continue heating to 1000-1100℃ at a rate of 2-5℃ / min and hold for 6-8 hours.
2. The method for preparing Ti-6Al-4V titanium alloy based on zirconium hydride regulation according to claim 1, characterized in that: In S1, the conditions for mixing the powder are as follows: the powder is mixed by ball milling under inert gas protection, the ball-to-material ratio is 1:(2~3), the ball milling speed is 150~250 r / min, and the ball milling time is not less than 10 h.
3. The method for preparing Ti-6Al-4V titanium alloy based on zirconium hydride regulation according to claim 2, characterized in that: In S1, the adhesive includes polyoxymethylene, high-density polyethylene, ethylene-vinyl acetate and stearic acid; The total amount of Ti-6Al-4V powder and zirconium hydride powder is used in a mass ratio of (85~87):(13~15) to the binder.
4. The method for preparing Ti-6Al-4V titanium alloy based on zirconium hydride regulation according to claim 3, characterized in that: The adhesive comprises, by weight percentage: 83-85% polyoxymethylene, 1-3% high-density polyethylene, 3-6% ethylene-vinyl acetate, and 8-10% stearic acid.
5. The method for preparing Ti-6Al-4V titanium alloy based on zirconium hydride regulation according to claim 1, characterized in that: In S2, The injection molding conditions are: temperature 180~190℃, pressure 90~120MPa; The catalytic degreasing process uses oxalic acid vapor as a catalyst, and the temperature is raised to 110~115℃, 120~122℃, and 125~127℃ respectively at a heating rate of 0.5~1.5℃ / min, and then kept at each temperature range for 1.5~2.5h.
6. A method for preparing Ti-6Al-4V titanium alloy based on zirconium hydride regulation according to claim 1 or 5, characterized in that: In S3, The heating program for the heat degreasing is as follows: the temperature is increased to four stages at a rate of 0.5~1.5℃ / min, namely 180~210℃, 320~350℃, 430~450℃, and 650~700℃, and each stage is held for 0.3~0.8h.
7. A Ti-6Al-4V titanium alloy based on zirconium hydride regulation obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The carbon content is less than 0.109 wt.% and the oxygen content is less than 0.324 wt.%.
8. An application of the Ti-6Al-4V titanium alloy based on zirconium hydride regulation as described in claim 7, characterized in that: It is used as a raw material in the preparation of titanium alloy components for medical devices.
Citation Information
Patent Citations
Oxygen control process for injection molding titanium alloy based on oxygen-free solvent degreasing
CN121267181A
Composite reinforced TC4 titanium alloy feed and preparation method of titanium alloy material
CN121826442A
Method for preparing high-density low-carbon-oxygen titanium alloy
CN120306643A